Wrigley's Eclipse gum : managing brand adolescence - Lee, Angela Y., (SAGE knowledge. Cases., 2016)
Wrigley launched Eclipse gum in August 1999. In early 2000, Paul Chibe became senior marketing manager for Wrigley's breath freshening portfolio, which included Eclipse. With the disappointing first-year performance of the brand, Chibe needed to take action to turn Eclipse around. His task was to use the opinions from other Wrigley executives and from marketing research data to decide if Eclipse could be turned around or if it should be abandoned.